Eklektisisme dalam Taqnīn Hukum Keluarga di Dunia Islam - Abdul Ghofur; Sulistiyono Sulistiyono (Islamica: Jurnal Studi Keislaman, 2014)
The Qur'ān was revealed with justice and equality for human beings regardless of their sex, race, social class, and ethnicity, as cardinal principles and intrinsic values in Islamic sharī'ah. If this is the case, modern Muslim society with Islamic law is necessarily of equality and justice. However, their family laws which are grounded on assumptions of past centuries and have little bearing on contemporary realities have not reflected gender relations. Inequality that occurs within the context of Muslim family laws is one of the subtle but most pervasive areas of discrimination against women. It has resulted in a different set of dynamics that help create new demands in favor of change of laws. This study explores the reform strategy through legal mobilization in the Muslim family laws around the world. The findings of the study reveal that the substantive and pluralistic legal mobilization is important to Muslims, and the reinterpretation and renewal of laws have been mobilizing debates among both proponents and opponents, framed by orientations to the modernists who advocate reinterpretation of the original sources and the traditionalists who insist on literal adherence to the received doctrinal corpus.